Case Report: A rare infection of multidrug-resistant Aeromonas caviae in a pediatric case with acute lymphoblastic leukemia and review of the literature - Dai, Yiling; Gao, Ju; Jiang, Mingyan (Frontiers in Pediatrics, 2024)
Aeromonas caviae infection of the bloodstream and intestine is a rare and severe opportunistic infection in immunocompromised people. In Southwest China, we first reported a case of bloodstream and intestinal infection with multidrug-resistant Aeromonas caviae in a 4-year-old child with T-cell acute lymphoblastic leukemia. Blood and stool cultures were used to identify the infection. The selection of antibiotics was based on clinical expertise and medication sensitivity tests. We used linezolid, levofloxacin, and polymyxin B to treat the patient aggressively. Aeromonas caviae infection is uncommon in juvenile acute lymphoblastic leukemia. Doctors should be aware of the likelihood of opportunistic infection during the post-chemotherapy bone marrow suppression period. We further conducted a review of the literature and performed a detail analysis of Aeromonas infection in pediatric leukemia. It is increasingly outstanding that antibiotic is abused in domestic and abroad, which results the multidrug resistant bacteria increased sharply. In general, most of the Aeromonas isolates are susceptible to third- or fourth-generation cephalosporins, aminoglycosides, quinolones and carbapenem, but drug resistant strains have been reported increasingly. We summarized the drug resistance rate of Aeromonas caviae and Aeromonas hydrophila in China for recent 10 years. Early recognition and effective treatment will improve prognosis and reduce mortality.